Horn antenna based on a foreign rectangular waveguide with partial dielectric filling and coupling loop - N.M. Каrashchuk; V.P. Маnoilov; Т.M. Nikitchuk; V.V. Chukhov; P.P. Martynchuk (Технічна інженерія, 2020)
The characteristics of the horn antenna based on the foreign rectangular waveguide with partial dielectric filling (PDF) and the communication loop are considered. The mirror method was chosen for the experimental measurement of the antenna gain. Accordingly, it is proposed to use a resonance model (rectangular resonator) for the analysis of such antennas. The formula for calculating the input resistance of the communication loop, which excites the resonator, is obtained. The formula takes into account the additional resistance in the loop circuit, which appears due to the excitation of the electromagnetic field in the resonator. This allows us to calculate the standing wave ratio (SWR) and the gain of the antenna in particular. Experimental measurements of the dependences of SWR on the change in the length, thickness of dielectric plates with relative dielectric constant and the diameter of the communication loop wire in a rectangular waveguide with dimensions of mm for a type wave were performed. Optimal dielectric plate sizes and communication loop positions are proposed to improve antenna alignment. The results of experimental measurement of the antenna gain are given, which do not have significant differences with the calculations. The considered dependences of the antenna gain have a resonant character, which indicates the correctness of the application of the resonant model for the analysis of such emitters.